Wastewater treatment and reuse in Morocco: situation and perspectives - Choukr-Allah R. (Non-conventional water use: WASAMED project, 2005)
Since the sixties, Morocco has largely contributed to the mobilization of its hydraulic capacities in order to face the demographic increase and sustain its social and economic development. Nonetheless, and in addition to the continuation of the efforts directed to mobilization, and the control of the demand, the limited hydraulic potential requires the resort to unconventional resources. The use of treated wastewater in irrigation is necessity for a better water resources economy. The present article deals with the experiences carried out in Morocco in this domain. In spite of the progress that has been achieved in the last decade on technical, institutional, financial and legislative levels as regards the development of the process 'sewage network-treatment-re-use', obstacles still hinder the deployment of the re-use of treated wastewater. In the current state of affairs, no project integrating the three components has been realized. This paradoxical situation is due to several constraints.
3. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2004/12/07-10, Cairo (Egypt)